Andrographolide suppresses breast cancer progression by modulating tumor‐associated macrophage polarization through the Wnt/β‐catenin pathway. (2nd August 2022) - Li, Lin; Yang, Li‐Li; Yang, Song‐Lin; Wang, Run‐Qing; Gao, Hui; Lin, Zhu‐Ying; Zhao, Yi‐Yi; Tang, Wei‐Wei; Han, Rui; Wang, Wen‐Ju; Liu, Ping; Hou, Zong‐Liu; et al.
Abstract: Andrographolide(ADE) has been demonstrated to inhibit tumor growth through direct cytotoxicity on tumor cells. However, its potential activity on tumor microenvironment (TME) remains unclear. Tumor‐associated macrophages (TAMs), composed mainly of M2 macrophages, are the key cells that create an immunosuppressive TME by secretion of cytokines, thus enhancing tumor progression. Re‐polarized subpopulations of macrophages may represent vital new therapeutic alternatives. Our previous studies showed that ADE possessed anti‐metastasis and anoikis‐sensitization effects. Here, we demonstrated that ADE significantly suppressed M2‐like polarization and enhanced M1‐like polarization of macrophages. Moreover, ADE inhibited the migration of M2 and tube formation in HUVECs under M2 stimulation. In vivo studies showed that ADE restrained the growth of MDA‐MB‐231 and HCC1806 human breast tumor xenografts and 4T‐1 mammary gland tumors through TAMs. Wnt5a/ β ‐catenin pathway and MMPs were particularly associated with ADE's regulatory mechanisms to M2 according to RNA‐seq and bioinformatics analysis. Moreover， western blot also verified the expressions of these proteins were declined with ADE exposure. Among the cytokines released by M2, PDGF‐AA and CCL2 were reduced. Our current findings for the first time elucidated that ADE could modulate macrophage polarization and function through Wnt5a signaling pathway, thereby playing its role in inhibition of triple‐negative breast cancer.